THE THINGKING OF ISLAMIC ECONOMY IN MUHAMMAD PROPHET ERA (PEMIKIRAN EKONOMI ISLAM PADA MASA NABI MUHAMMAD) - Fauzan, Ibnudin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
The article aims to explore the thinking of Islamic economic in Muhammad prophet era. Islamic economic is the economic system which based on Islamic values which based on holly Alquran and hadis. The purpose of Islamic economic implementation is to create civil society. Muhammad prophet as a model for all human being in various of life aspect transformed economic system to bring the goodness to all human race. Before Islamic era, prophet Muhammad officiate as leader and messenger of Allah so that change the economic system and state financial appropriated the Alquran and hadis. Moreover prophet Muhammad was the first pioneer to implement Islamic economic policy.